The Direct Dissolution of Ion-Exchange Resin by Fenton's Reagent - 김길정; 손종식; 류우석; Kil-Jeong Kim; Jong-Sik Shon; Woo-Seog Ryu (Journal of nuclear fuel cycle and waste technology (Online), 2007)
양이온교환수지인 IRN-77을 직접 분해 처리하기 위하여 Fonton시약을 적용하였으며, 분해반응의 특징으로써 반응의 효율 및 안전을 위해 수지를 먼저 건조시키고 용액을 수지에 완전히 흡수시킨 후 를 첨가하는 방법을 적용하였다. 수지 분해반응의 특성은 반응이 개시되기까지 반응유도시간이 필요하였으며, 반응유도시간은 의 농도가 낮을수록 또한 의 초기 첨가량이 적을수록 길었다. 단위량의 수지를 분해하는데 적절한 반응조건으로서 의 농도는 0.9 M 및 15% 의 용액의 첨가량은 수지량에 대해 6-7배 비율로 나타났으며, 반응유도시간을 포함하여 1.5시간 이내에 완전 분해가 가능하였다. 의 첨가방법은 반응 초기 및 반응개시 후로 나누어 첨가하므로서 의 분해효율 및 첨가량을 최소화하였다. 가열효과로서 분해반응 개시 전에 비교적 낮은 온도인 정도로 가열하면 반응유도시간이 5분 이내로 단축되었으며, 수지의 양을 5g 및 10g 으로 증가시킨 결과, 의 첨가비율을 9-10배 정도로 증가시키면 완전분해가 가능하였다. Fenton's Reagent is applied to directly dissolve the cation-exchange resin, IRN-77. The characteristics of the experimental procedure is to dry the resin first and solution is completely absorbed into the resin, and then is introduced later for an effective reaction between the reagents within the resin. An a characteristic of the dissolution, the lag time is needed for about 1 hour until the main reaction is occurred, which was more affected with the less concentration of and the less initial dose of . The dose of was equally divided into the early stage and the later stage after the initial reaction to provide an effective and safe reaction condition. The optimum conditions is appeared that the concentration of is 0.9M and the dose of 15% solution is 6-7 volume for the dissolution of unit weight of IRN-77. The effect of the heating on the lag time was checked and the time could be reduced within 5 minutes at , which is a relatively low temperature. The large amount of the resin, 5g and 10g, was also completely decomposed by increasing the dose of to 9-10 volume ratio.